Nutrient ingestion increased mTOR signaling, but not hVps34 activity in human skeletal muscle after sprint exercise. - MURRAY, JAMES (My University, 2013)
Nutrient provision after sprint exercise enhances mammalian target of rapa- mycin (mTOR) signaling. One suggested that nutrient sensor is the class III phosphatidylinositol 3-kinase, vacuolar protein sorting 34 (Vps34), not previ- ously studied in human skeletal muscle. It is hypothesized that oral ingestion of essential amino acids (EAA) and carbohydrates (Carb) increases Vps34 activity and mTOR signaling in human skeletal (hVps34) muscle after sprint exercise. Nine subjects were performed 3 9 30-sec all-out sprints with or without ingestion of EAA + Carb or placebo drinks in a randomized order with a month interval. Muscle biopsies were performed at rest and 140 min after last sprint and analyzed for p-mTOR, p-p70S6k, p-eEF2 and for hVps34 activity and hVps34 protein content. Venous blood samples were collected and analyzed for amino acids, glucose, lactate, and insulin. During the sprint exercise session, EAA, glucose, and insulin in blood increased significantly more in EAA + Carb than in placebo. P-mTOR and p-p70S6k were signifi- cantly increased above rest in EAA + Carb ( P = 0.03, P = 0.007) 140 min after last sprint, but not in placebo. Activity and protein expression of hVps34 were not significantly changed from rest in EAA + Carb 140 min after the last sprint. However, hVps34 activity and protein expression tended to increase in placebo (both P = 0.08). In conclusion, on the contrary to the hypothesis, no increase in activation of hVps34 was found following sprint exercise in EAA + Carb condition. In spite of this, the results support an activation of mTOR during this condition. However, this does not exclude the permissive role of hVps34 in mediating the amino acid-induced activation of mTOR and muscle protein synthesis.
PUBLISHED
Keywords: Biochemistry; Ageing